Cascading extinctions as a hidden driver of insect decline. (30th November 2020) - Kehoe, Rachel; Frago, Enric; Sanders, Dirk
Abstract : 1. The decline in insect abundance and diversity observed in many ecosystems is of major concern because of the long‐term consequences for ecosystem function and stability. 2. Species in ecological communities are connected through interactions forming complex networks. Therefore, initial extinctions can cause further species losses through co‐extinctions and extinction cascades, where single extinctions can lead to waves of secondary extinctions. Such knock‐on effects can multiply the initial impact of disturbances, thereby largely adding to the erosion of biodiversity. However, our knowledge of their importance for the current insect decline is hampered because secondary extinctions are challenging to both detect and predict. 3. In this review, we bring together theory and knowledge about secondary extinctions in the light of the main drivers of insect decline. We evaluate potential and evidence for cascading extinction for the different drivers and identify major pathways. By providing selected examples we discuss how habitat loss, pollution, species invasions, climate change and overexploitation can cause cascading extinctions. We argue that habitat loss and pollution in particular have the largest potential for such extinctions by changing community structure, the physical environment, and community robustness. 4. Overall, cascading extinction are part of an ecosystems' response to anthropogenic drivers but are so far not explicitly measured in their contribution when evaluating biodiversity loss. This knowledge is necessary to predict biodiversity loss and find strategies to buffer against the devastating long‐term impact of habitat loss, pollution, species invasions, and climate change. Abstract : Initial biodiversity loss can cause further species losses through co‐extinctions and extinction cascades multiplying the initial impact and thereby largely adding to the erosion of biodiversity. We discuss how habitat loss, pollution, species invasions, climate change, and overexploitation can cause cascading extinctions in insects by changing community structure, the physical environment, and community robustness. Overall, cascading extinction are part of an ecosystems' response to anthropogenic drivers but need to be more explicitly measured in their contribution when evaluating biodiversity loss.